2016
DOI: 10.1017/s1368980016001324
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of forest foods to dietary intake and their association with household food insecurity: a cross-sectional study in women from rural Cameroon

Abstract: Objective: To determine the contribution of forest foods to dietary intake and estimate their association with household food insecurity. Design: Cross-sectional survey conducted among 279 households. Using a 7 d recall questionnaire, information on household food consumption was collected from women and used to determine the household dietary diversity score, food variety score and forest food consumption score (FFCS). Household Food Insecurity Access Scale (HFIAS) score was determined and Spearman rank corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 36 publications
(76 reference statements)
4
47
1
Order By: Relevance
“…While a low diversity of wild plants was also observed in the diet of other hunter-gatherers in the Congo Basin (de Garine 1996b;Ichikawa 1996;Termote et al 2012), the decrease of these wild plants in the environment is a concern for both local biodiversity and livelihood. Reducing amounts of wild plants in Baka daily meals will have an impact on their food security, given the recognized importance of wild species for the diversity of micronutrients they provide (Erskine et al 2014;Fungo et al 2016). Moreover, this is accompanied by a potential loss of local knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…While a low diversity of wild plants was also observed in the diet of other hunter-gatherers in the Congo Basin (de Garine 1996b;Ichikawa 1996;Termote et al 2012), the decrease of these wild plants in the environment is a concern for both local biodiversity and livelihood. Reducing amounts of wild plants in Baka daily meals will have an impact on their food security, given the recognized importance of wild species for the diversity of micronutrients they provide (Erskine et al 2014;Fungo et al 2016). Moreover, this is accompanied by a potential loss of local knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For the top forest dependent communities across these countries, forest food products provide nearly 15% of the recommended quantities of fruits and vegetables, and 106% for meat and fish (Rowland et al, 2017). Fungo et al (2016) report that forest foods contribute 93% of daily vitamin A intake of women in rural forest-dependent communities in Cameroon.…”
Section: Underlying Determinants Of Undernutrition Addressed By Forestsmentioning
confidence: 99%
“…The findings contrast with the established contribution of wild foods in rural contexts, where wild foods are positively associated with diversifying diets. Fungo et al [65], drawing upon evidence from 11 villages across the eastern-southern Cameroon, found that households who consumed forest foods displayed higher dietary diversity as compared to those who did not, as did Maseko et al [66] amongst children in Malawi. Similarly, Luna-González and Sørensen [67] observed a direct positive relationship between dietary diversity and wild food from six villages in Baja Verapaz, Guatemala.…”
Section: The Contribution Of Wild Foods To Household Dietary Diversitymentioning
confidence: 94%